Ville durable et nouveaux territoires du corps - Guy Di Méo; Karen Foussette (Développement Durable et Territoires)
In Bordeaux, city-dwellers’ relations to their bodies incite them to practice physical exercises more and more often and to present themselves in original and individualistic ways asserting their identities. This leads them to explore the city and exploit its growing resources (cycle tracks, sports arenas, familial gardens, pedestrian areas, tattoo-shops, and various other accommodations) until they mix their bodies with the places in which their practices take place. More than the controversial building of eco-neighbourhoods, more than discourses on local democracy (that has aborted) or sustainable development (that is very blurred), this new spatial corporeity and its exigencies in terms of urban transparency (that is to say in terms of environmental and socio-spatial justice desire, of security and civility, of nature) polarize the political stakes of the sustainable city.